Análisis de la relación Estado moderno y capital: aproximaciones metodológicas - Fallas Jiménez, Yessenia Isabel (2022)
Introduction: This text is part of the results of the Research project Historical foundations of the genesis of the modern State and its relationship with capitalist production. This research allowed to investigate the historical determinations that shape the relationship between modern State and capital, understanding that the configuration of the elements that allowed the rise of capital required the existence of a political structure that accompanied the accumulation process. Objective: One of the specific objectives of the research establishes the following: "To elaborate a proposal of theoretical foundation for the critical understanding about capitalist production, the modern State and the historical relationship between both". As a derivation of this objective, some elements of methodological character that guide the analysis of the State and its relation with capitalist production were studied. Method: Given the nature of the research, we resorted to the analysis of secondary sources oriented to the discussion of historical processes referred to the State and capitalist production, as well as to bibliography proper to Marxist theoretical production in order to identify existing debates. Results: Specifically in this article we will expose reflections on methodological aspects that as a result of the research process itself, become proposals for approaching and understanding both categories. Conclusions: From this research, the need to understand the objects of study from broader historical processes emerges, identifying the way in which mediations with general history are configured as contradictory constituents of such objects.